Evaluation of bladder and bowel functions in children with microcephaly and congenital zika syndrome. Issue 5 (October 2021) - Azevedo de Almeida, Valéria; Gonçalves, Rafael Pauletti; Morya, Edgard; Cavalcanti Simas, Luiza Emilia; Rodrigues Arrais, Nivia Maria; Lisboa, Lilian Lira; Costa Monteiro, Lucia Maria; Antônio de Oliveira Freitas Júnior, Reginaldo
Summary: Introduction: Children with Congenital Zika Syndrome (CZS) present structural cortical changes that may compromise the integrity of their connections with urinary and digestive systems, causing bowel and bladder dysfunctions. Objective: To evaluate bladder and bowel dysfunction (BBD) in children with CZS. Study design: This is an observational cross-sectional study of a series of CZS cases. Urinary tracts were investigated using a bladder function protocol consisting of clinical history, detailed physical examination, laboratory tests, ultrasound of the lower and upper urinary tracts, and urodynamic evaluation. The bowel function protocol expanded anamnesis with questions related to signs and symptoms of functional disorders, Bristol scale, and ultrasound of the rectal ampoule. Results: Forty children with CZS, aged between one and five years were included. The majority (80%) had bladder and bowel dysfunction (BBD), 12.5% had bladder dysfunction only, and 7.5% only bowel dysfunction. A reduced bladder capacity was confirmed in 36 patients (90%), while 15 (40%) presented postvoid residual greater than 20% of their cystometric capacity. Thirty-five patients (87.5%) presented four signs/symptoms of functional bowel disorders and the rectal ampoule ultrasound was >2.9 cm in 21 (52.5%). Moreover, 19 (47.5%) presented urinary tract infection, while 5 (12.5%) developed pyelonephritis and required hospitalization. Renal ultrasound showed nephrolithiasis in three (7.5%), one (2.5%) presented horseshoe kidney, and a duplicated collecting system was found in three patients. Cryptorchidism was presented in eight (34%). Discussion: Our study confirmed the presence of BBD in 80% of the children with CZS studied in this series. This is the first time that bowel dysfunction is confirmed in the settings of CZS. This recognition will facilitate early identification and appropriate therapies in an attempt to reduce complications. One limitation of the study is the absence of a control group. Due to the new aspects of CZS, it has been difficult to find a suitable group of patients with neurological disorders to compare and performing urodynamic studies in children without neurological or non-neurological voiding dysfunction is unethical. Appropriate control groups for future studies may be children with microcephaly due to other causes or older children with CZS who were not yet investigated or treated. Another limitation is the lack of a standard quantitative evaluation of bowel dysfunction in children with neurological disorders. Summary Figure Most children 32 (80%) had bladder and bowel dysfunction, 5 (12.5%) had only bladder dysfunction, and 3 (7.5%) only bowel dysfunction. Summary Figure Conclusion: Bladder and bowel dysfunction was confirmed in 80% of the children with CZS. This is a new Zika virus-associated neuromuscular disorder that needs to be further investigated.